Erratum. (July 2017) - Unknown
Simulation 2017; 93(3): 185-200 Abir Ben Khaled-El Feki, Laurent Duval, Cyril Faure, Daniel Simon and Mongi Ben Gaid CHOPtrey: Contextual online polynomial extrapolation for enhanced multi-core co-simulation of complex systems Doi:10.1177/0037549716684026